2014
DOI: 10.1016/j.pec.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes self-management programs on time-to-hospitalization among patients with type 2 diabetes: A survival analysis model

Abstract: Objective This study compared time-to-hospitalization among subjects enrolled in different diabetes self-management programs (DSMP). We sought to determine whether the interventions delayed the occurrence of any acute event necessitating hospitalization. Methods Electronic medical records (EMR) were obtained for 376 adults enrolled in a randomized controlled trial (RCT) of Type 2 diabetes (T2DM) self-management programs. All study participants had uncontrolled diabetes and were randomized into either: person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The results of the present study are consistent with three previous studies [14][15][16] which examined the effects of a diabetes education programme on hospital service utilization over a prolonged follow-up period. A structured diabetes education group in a Korean study had a significantly lower frequency of diabetes-related hospitalizations than a control group after a median follow-up of 4 years, and results from a retrospective cohort study showed that an education programme was significantly associated with delaying first hospitalization events.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are consistent with three previous studies [14][15][16] which examined the effects of a diabetes education programme on hospital service utilization over a prolonged follow-up period. A structured diabetes education group in a Korean study had a significantly lower frequency of diabetes-related hospitalizations than a control group after a median follow-up of 4 years, and results from a retrospective cohort study showed that an education programme was significantly associated with delaying first hospitalization events.…”
Section: Discussionsupporting
confidence: 92%
“…The impact of PEP on CVD benefit might be attributable to improvement in intermediate outcomes such as metabolic control through empowerment of self-care and the enhancement of quality of diabetes care in primary care. Nonetheless, given the paucity of longitudinal data on observed events among subjects who do or do not take part in diabetes education programmes, only the association of a diabetes education programme with occurrence of diabetes-related hospitalization has been investigated to date [22]. A recent study showed that subjects enrolling in an education programme generally had a significant HR of 0.10 (95% CI 0.023-0.438; p = 0.002) of being hospitalized because of diabetes-related acute events when compared with subjects in a control group.…”
Section: Discussionmentioning
confidence: 99%
“…In heart failure, self-care reduces hospitalization rates , health-care costs (Hamar et al, 2015) and mortality (Smith et al, 2014), and improves quality of life (Clark et al, 2015). In diabetes mellitus, self-care improves metabolic control , Yuan et al, 2014 and quality of life (Chao et al, 2015, Kargar Jahromi et al, 2015 and reduces cardiovascular risk (Powers et al, 2015, Sicuro et al, 2014, hospitalizations (Adepoju et al, 2014) and disease-related complications (Kargar Jahromi et al, 2015, Shreck et al, 2014, Williams et al, 2014. Unfortunately, self-care is suboptimal in both heart failure and diabetes mellitus patients , Dunbar et al, 2014, Dungan et al, 2013, Jaarsma et al, 2013, Kerr et al, 2007, Saleh et al, 2014, Ware et al, 2006, and when more than one illness is active, self-care becomes particularly challenging (Gallacher et al, 2011, Schmitt et al, 2014.…”
Section: Introductionmentioning
confidence: 99%